(untitled) (Research, Society and Development, 2021)
Introduction: Currently, there is a high rate of patients with signs and symptoms of temporomandibular disorders, of multifactorial etiology. Dental wear and clamping are the main complaints characterized by bruxism. In addition to affecting aesthetics, this change is responsible for modifying the patient’s occlusion, impairing the relationship and distribution of forces between antagonistic teeth. It is known that, within the concept of mutually protected occlusion, the anterior teeth can receive oblique forces, while the posterior teeth receive the vertical ones. However, with the absence of a canine guide, during mandibular laterality movement, the posterior teeth present poorly distributed contacts, generating oblique masticatory forces, resulting in wear and interference, compromising the stomatognathic system. Objective: To describe procedures performed on a patient with a history of bruxism, returning a canine guide through the use of E-max ceramic fragments. Clinical case report: The absence of a canine guide was observed, whose treatment of choice was the reestablishment of the anatomical characteristics of the canines with fragments made in ceramics, occlusal adjustment, and a subsequent indication of continuous use of myorelaxant plaque in acrylic resin. Result in Functional treatment with satisfactory aesthetics and reestablishment of the patient’s canine guide and its mutually protected occlusion. Conclusion: The reported treatment with ceramic fragments favored excursive mandibular movements and returned physiological aspects of the occlusion, contributing to the improvement of the signs and symptoms of bruxism and the patient’s quality of life.